2008
DOI: 10.1016/j.neuroscience.2008.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the amygdala and medial prefrontal cortex to incentive cue responding

Abstract: Reward-seeking behavior is controlled by neuronal circuits that include the basolateral nucleus of amygdala (BLA), medial prefrontal cortex (mPFC), nucleus accumbens (NAc) and ventral tegmental area. Using a discriminative stimulus (DS) task in which an intermittently presented cue (DS) directs the animals to make an operant response for sucrose, we previously demonstrated that dopamine receptor antagonism in the NAc reduced reinforced cue responding, whereas general inactivation of the NAc increased behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 51 publications
4
80
0
Order By: Relevance
“…For example, activity is increased in IL neurons following cue-and context-induced cocaine and heroin seeking, and IL inactivation diminishes reinstatement of extinguished cocaine, methamphetamine, and heroin seeking (7). Furthermore, PL inactivation increases spontaneous and premature behaviors (8)(9)(10) and impairs response inhibition (11). Together, these results imply that neuronal networks within PL and IL can contribute to both response execution and inhibition.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, activity is increased in IL neurons following cue-and context-induced cocaine and heroin seeking, and IL inactivation diminishes reinstatement of extinguished cocaine, methamphetamine, and heroin seeking (7). Furthermore, PL inactivation increases spontaneous and premature behaviors (8)(9)(10) and impairs response inhibition (11). Together, these results imply that neuronal networks within PL and IL can contribute to both response execution and inhibition.…”
Section: Discussionmentioning
confidence: 95%
“…PL inactivation during discriminative stimulus (DS)-driven reward-seeking reduces cue-driven behaviors (8). However, PL inactivation also increases nonspecific (8) and premature lever responding (9,10), and PL is important in inhibiting responses during a stop-signal reaction time task (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As the neural circuits that include the nucleus accumbens, amygdala, and prefrontal cortex are known to have crucial roles in emotions, motivation, and reward (Cardinal et al, 2002;Carlezon and Thomas, 2009;Ishikawa et al, 2008;Kalivas and Nakamura, 1999), we examined the effects of encounter stimulation on c-Fos expression in these brain regions. Encounter stimulation increased c-Fos expression in the nucleus accumbens shell of group-and isolationreared mice to a similar degree.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies that used projection-specific targeting to study amygdala function highlight how activity in one brain region may mediate distinct behavioral responses depending on the strength and pattern of activity that it communicates to specific downstream targets Tye et al, 2011). The amygdala is a critical structure for processing negative emotions, such a fear (Fanselow and Gale, 2003;Pare et al, 2004;Ehrlich et al, 2009;LeDoux, 2012), but also plays an integral role in the encoding and behavioral responses to salient environmental cues of both negative and positive valence (Paton et al, 2006;Ambroggi et al, 2008;Ishikawa et al, 2008;Tye et al, 2008;Shabel and Janak, 2009;Gardner, 2011). Pathway-specific optogenetic modulation of the glutamatergic projection from the BLA to the nucleus accumbens (NAc), including the activation and inactivation of BLA terminals in the NAc, confirmed that this circuitry is both necessary and sufficient for cue-driven motivated behavior .…”
Section: A Strengths Of the Optogenetic Approachmentioning
confidence: 99%